Knowledge of Parents and Guardians of Computed Tomography Examinations and Radiation Risks in Children in Malaysia - Ali Wahab, Nur Maisarah; Mohd Zainudin, Nur Hamizah (UI Scholars Hub, 2026)
Background: Early exposure to computed tomography (CT) imaging during childhood increases cancer risk, emphasizing the critical need to minimize unnecessary imaging in pediatric patients. This study aimed to assess parents and guardians’ knowledge about CT examinations and their associated risk following pediatric CT. Methods: A cross-sectional survey was conducted among parents and guardians who accompanied their children to a private hospital radiology department for CT examinations. The survey enquired about their socio-demographic, knowledge of CT examinations, and their radiation risks. Data were analyzed using descriptive analysis and the Kruskal-Wallis test. Results: A total of 144 responses were received in this study. The respondents have a good knowledge of CT examinations and their risks, with a mean score of 4.06 ± 0.33. Most respondents (99%) agreed that CT scan results help diagnose and plan treatment for their child. Most respondents (99%) recognized that children are more vulnerable to cancer from radiation than adults. However, many were uncertain about the specific health risks of CT scans. Knowledge of CT and radiation risks differed significantly by respondents’ roles and occupations. (p < 0.05). Conclusions: Parents and guardians are well-versed in CT examinations, but they are unaware of the radiation risks to their children, emphasizing the importance of pediatric CT education.